2023
DOI: 10.3390/ijms242015066
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Histone Deacetylases in the Regulation of Ovarian Cancer Metastasis

Long Xu,
Xiaoyu Yan,
Jian Wang
et al.

Abstract: Ovarian cancer is the most lethal gynecologic malignancy, and metastasis is the major cause of death in patients with ovarian cancer, which is regulated by the coordinated interplay of genetic and epigenetic mechanisms. Histone deacetylases (HDACs) are enzymes that can catalyze the deacetylation of histone and some non-histone proteins and that are involved in the regulation of a variety of biological processes via the regulation of gene transcription and the functions of non-histone proteins such as transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 158 publications
0
2
0
Order By: Relevance
“…In the last decade, a variety of compounds that can block the deacetylase activity of HDACs have been recognized, and synthetic or natural molecules targeting class I, II, and IV HDACs have been developed [29]. Moreover, preclinical studies have found that HDAC inhibitors (HDACis) are able to inhibit ovarian cancer cell growth in vitro and in vivo by inhibiting the cell cycle and inducing mitotic defects through histone-mediated and histone-independent interactions [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, a variety of compounds that can block the deacetylase activity of HDACs have been recognized, and synthetic or natural molecules targeting class I, II, and IV HDACs have been developed [29]. Moreover, preclinical studies have found that HDAC inhibitors (HDACis) are able to inhibit ovarian cancer cell growth in vitro and in vivo by inhibiting the cell cycle and inducing mitotic defects through histone-mediated and histone-independent interactions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preclinical studies have found that HDAC inhibitors (HDACis) are able to inhibit ovarian cancer cell growth in vitro and in vivo by inhibiting the cell cycle and inducing mitotic defects through histone-mediated and histone-independent interactions [30]. Recently, numerous clinical trials investigate the role of HDACis alone or in combination with other drugs in patients with epithelial ovarian cancer, showing encouraging anti-tumor effects [29], especially when combined with other chemotherapeutics. This combination seems to show chemosensitizing or synergistic antitumor efficacy, which may be due to their ability to overcome particular mechanisms associated with drug resistance [31].…”
Section: Discussionmentioning
confidence: 99%